Structure and Pragmatics of Demonyms in South America - S. Chesnokova, Olga; Radović , Marija; R. Tejerina Ledesma, Guido (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the authors examine and systematize demonyms in South American Spanish and Brazilian Portuguese. The aim of the present investigation consists in studying, defining, and analyzing the main trends in the formation of the denominative adjectives (that become demonyms when adopting the meaning of nouns) and establishing the parameters of differences and convergences in South America while analyzing the motivation sources, grammar formulae, principles of suffix combinations, their cultural variants, and cases of toponymic homonymy. The methodology for such a study has included historic, linguistic, and semiotic analysis. The main results confirm the hypothesis that there is a non-systematic alternation of suffixes used for deriving demonyms, as well as the existence of other morphological and pragmatic tendencies.